2009
DOI: 10.1109/tcomm.2009.12.080559
|View full text |Cite
|
Sign up to set email alerts
|

On the limits of communication with low-precision analog-to-digital conversion at the receiver

Abstract: Abstract-As communication systems scale up in speed and bandwidth, the cost and power consumption of high-precision (e.g., 8-12 bits) analog-to-digital conversion (ADC) becomes the limiting factor in modern transceiver architectures based on digital signal processing. In this work, we explore the impact of lowering the precision of the ADC on the performance of the communication link. Specifically, we evaluate the communication limits imposed by low-precision ADC (e.g., 1-3 bits) for transmission over the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
189
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(193 citation statements)
references
References 26 publications
4
189
0
Order By: Relevance
“…We begin by recalling some results we obtained last year while investigating these issues for the classical bandlimited Additive White Gaussian Noise (AWGN) channel [3], [4]. Apart from its fundamental significance, the AWGN channel model also forms an excellent approximation for the near line-of-sight, 60 GHz "point-and-shoot" links, where the use of directional antennas (possibly fixed beam) at each end can cut down drastically on multipath.…”
Section: Transceiver Design With Low-precision Adcmentioning
confidence: 99%
“…We begin by recalling some results we obtained last year while investigating these issues for the classical bandlimited Additive White Gaussian Noise (AWGN) channel [3], [4]. Apart from its fundamental significance, the AWGN channel model also forms an excellent approximation for the near line-of-sight, 60 GHz "point-and-shoot" links, where the use of directional antennas (possibly fixed beam) at each end can cut down drastically on multipath.…”
Section: Transceiver Design With Low-precision Adcmentioning
confidence: 99%
“…Specifically, in [2], we have shown analytically that for the extreme scenario of 1-bit symmetric quantization, binary antipodal signaling achieves the capacity (at any SNR). Multi-bit quantization has been considered in [3], [10], where we show that the cutting-plane algorithm [11] can be employed for computing the capacity and obtaining optimal input distributions.…”
Section: Capacity Computationmentioning
confidence: 99%
“…{jsingh, madhow}@ece.ucsb.edu, onkar@tcs.tifr.res.in capacity for any signal-to-noise ratio (SNR) [2]. For multibit quantization [3], we provided a duality-based approach to bound the capacity from above, and employed the cuttingplane algorithm to generate input distributions that nearly achieved these upper bounds. Based on our results, we conjectured that a discrete input with cardinality not exceeding the number of quantization bins achieves the capacity of the average power constrained AWGN-QO channel.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], it has been shown that quantization causes floors in the bit error performance in single-input multiple-output (SIMO) fading channels. In [3], it is shown that for a single-input single-output (SISO) pointto-point single user system with additive white Gaussian noise (AWGN), receiver quantization with low precision ADC results in significant loss of capacity when compared to an unquantized receiver.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], the optimum input distribution for a point-to-point single-user SISO AWGN This work was supported in part by the DRDO-IISc Program on Advanced Research in Mathematical Engineering. channel with quantized output was shown to be non-Gaussian with a finite support set.…”
Section: Introductionmentioning
confidence: 99%